Ảnh hưởng của bão từ tới nồng độ điện tử tổng cộng vùng dị thường điện ly xích đạo Đông Nam Á quan sát được từ số liệu GPS - Minh, Lê Huy; Thắng, Nguyễn Chiến; Lan, Trần Thị; Fleury, R.; Duchesne, P. Lassudrie; Bourdillon, A.; Mazaudier, C. Amory-; Nam, Trần Ngọc; Lan, Hoàng Thái (Vietnam Journal of Earth Sciences, 2007)
The effect of the geomagnetic storm on the ionospheric total electron content in the Southeast Asian equatorial ionization anomaly region observed bY the GPS data